The Role of Civil Society in Promoting People, Democratic Space and Social Work: - (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Civil society formation and dissemination demonstrates society's solidarity and maneuvers towards authors. According to civil society's origins, civil society means that civil society demands are shown in a nonviolent and organized manner in such a way that civil society is quickly reactant to the divergence of authoritarians from the interests of society and the land. The government is responsible to the people and is able to persuade society to make its choices. The civic society movement is most significant because of the importance of public interests.